Pendekatan Hasan Al-Banna Dalam Mendamaikan Aliran Salaf Dan Khalaf: Kajian Dan Penilaian: Hasan Al-Banna’s Approach In Reconciling The Flow Of Salaf And Khalaf: Study And Evaluation - Nasron Yaacob (RABBANICA - Journal of Revealed Knowledge, 2023)
The article is about the similarities in the understanding and method of faith between the Salaf and Khalaf schools. The Khalaf belief system is ta’wil, whereas the Salaf belief system is ithbat or tafwid. Hasan al-Banna claims that these two schools of thought, though they approach the subject of God’s khabariyyah nature differently, are actually in agreement on three things. The methodology of the study is a qualitative study, sourced from documentation and authoritative works about the methods of the Salaf and Khalaf with reference to the issue of the nature of Allah’s khabariyyah. The work of Hasan al-Banna, particularly the book al-’Aqa’id, is emphasized to clarify three suggestions meant to address the disagreements between the Salaf and Khalaf over the nature of khabariyyah. The information data was also taken from the authoritative books of the scholars that represent the methods of their respective faiths. According to the research, it turned out that each of the Salaf and Khalaf have and acknowledge three common points in their understanding of the nature of khabariyyah as claimed by Hasan al-Banna. In that regard, this agreed point of commonality should be able to understand each trend in order to be open to celebrating disagreements and differences of opinion and methods that apply. Moreover, the difference of opinion involves the issue of ijtihad and branches of belief. The contribution of this study is to demand the issue of the unification of the ummah which needs to be prioritized instead of increasing differences of opinion until they are divided due to matters of ijtihad. The study is also expected to open a more harmonious and scientific discussion regarding these three points of commonality.Similarly, this research presents an argument in favour of promoting tolerance and intellectual dispute as a means of preserving. Kupasan artikel adalah berkenaan titik-titik persamaan dalam pemahaman dan metode akidah di antara aliran Salaf dan Khalaf. Metode akidah Salaf ialah ithbat atau tafwid, manakala metode akidah Khalaf ialah ta’wil. Hasan al-Banna mendakwa kedua-dua aliran ini yang berbeza metode mengenai topik sifat khabariyyah Allah adalah sebenarnya bersefahaman melalui tiga titik persamaan. Metodologi penulisan artikel adalah berasaskan kajian kualitatif, bersumberkan dokumentasi dan karya-karya muktabar tentang metode Salaf dan Khalaf berkenaan isu sifat khabariyyah Allah. Karya Hasan al-Banna sendiri khususnya risalah al-‘Aqa’id diketengahkan dalam perbincangan ini bagi menjelaskan tiga titik cadangan sebagai penyelesaian terhadap perbezaan pendapat di antara Salaf dan Khalaf berkenaan sifat khabariyyah. Data-data maklumat juga diambil daripada kitab-kitab muktabar para ulama yang mewakili metode akidah masing-masing. Berdasarkan kajian yang dilakukan, ternyata setiap aliran Salaf dan Khalaf memiliki dan mengakui tentang tiga titik persamaan dalam kefahaman terhadap sifat khabariyyah sebagaimana yang didakwa oleh Hasan al-Banna. Sehubungan itu, titik persamaan yang disepakati ini sepatutnya dapat memahamkan setiap aliran agar bersikap terbuka dalam meraikan perselisihan dan perbezaan pendapat dan metode yang berlaku. Lebih-lebih lagi perbezaan pendapat tersebut adalah melibatkan isu ijtihad dan cabangan akidah. Sumbangan daripada kajian ini adalah menuntut isu penyatuan ummah yang perlu diutamakan berbanding membesarkan perbezaan pendapat sehingga berpecah-belah disebabkan perkara ijtihad. Kajian juga diharap dapat membuka ruang perbincangan yang lebih harmoni dan ilmiah tentang tiga titik persamaan ini, di samping mencari titik-titik persamaan lain yang seterusnya melalui kajian lanjutan nanti. Demikian juga kajian ini menawarkan kempen kesatuan ummah melalui adab perselisihan pendapat yang berintelektual dan bertolak ansur.